Oral clindamycin and rifampicin combination therapy for hidradenitis suppurativa: a prospective study and 1‐year follow‐up. (1st December 2016) - Dessinioti, C.; Zisimou, C.; Tzanetakou, V.; Stratigos, A.; Antoniou, C.
Summary: Background: Limited data exist on the use of systemic antibiotic treatment for hidradenitis supportive (HS). Aim: To investigate the effectiveness, safety and relapse rate of HS treated with a combination of daily oral clindamycin and rifampicin. Methods: This was a prospective, hospital‐based study of oral clindamycin 600 mg and rifampicin 600 mg daily for 12 weeks for treatment of HS. Patients were followed up for 1 year to monitor for relapse. Results: In total, 26 patients with HS received oral clindamycin and rifampicin. Most were overweight or obese (73%), and most were smokers (88%). After 12 weeks, clinical response was noted in 19 patients (73%). Response was associated only with female sex ( P = 0.02), and not with body mass index, Hurley stage or lesion location. Eight patients (31%) experienced adverse events. At the 1‐year follow‐up, there was sustained efficacy in 7 (41%) patients, while 10 (59%) had disease relapse after a mean time of 4.2 months. Conclusions: Oral clindamycin with oral rifampicin for 12 weeks is an effective and tolerable regimen for HS.